Optimal Bidding and Generation Scheduling of Utilities Participating in Single Side Auction Markets Including Ancillary Services - B. Rampriya (Institute of Advanced Engineering and Science, 2018)
This paper presents the solution for the supplier’s profit maximization problem with unit commitment decisions participating in single side auction markets of a deregulated power system. The bids from market participants are received by a central pool mechanism and the Market Clearing Price (MCP) for energy and spinning reserve is fixed. The bid quantities are optimized using Differential Evolution (DE) algorithm. The supplier aims to achieve (more) profit than that of the rival’s participating in the competition. A GENCO with 6-unit participating in 24-hour day ahead energy and spinning reserve market is used to illustrate the methodology. The bidding parameters of rival’s participating in the competition are calculated by multi-variant Probability Density Functions (PDF). The results of the proposed methodology are compared with Refined Genetic Algorithm (RGA). Numerical results illustrate the effectiveness of the method in solving the supplier profit maximization problem.